Regulation and Competition : How Antitrust and Sector Regulation Affect Telecom Competition - Kerf, Michel (World Bank, Washington, DC, 2012)
Countries with fully liberalized telecommunications markets have adopted different mixes of antitrust and sector-specific regulatory instruments. Does the balance between the two approaches matter for competitiveness? Drawing on the experiences of Australia, Chile, New Zealand, the United Kingdom, and the United States, this Note finds that it does matter. Countries that get the balance right tend to have more competitive telecommunications markets.